The effective annual interest rate is:
i = (1 + 0.064/12)^12 - 1 = 0.066
In year 1: the interest is $613.80 (multiple $9300 by 0.066)
In year 2: the interest is $654.31 (add interest from year 1 to $9300 and multiply by 0.066)
In year 3: the interest is $656.98 (do the same as year 2)
In year 4: the interest is $657.16
The total interest is: $2582.25
The present worth of this amount is:
P = 2582.23 / (1 + 0.066)^4 = $1999.72
The answer is $1999.72.
Answer:
For this answer, I will label the points. Starting at the top left, then top right, then bottom left and bottom right let the points be A, B, C, D.
The new coordinates will be
A(-4,10)
B(4,10)
C(-4,4)
D(4,4)
Step-by-step explanation:
The question is asking for a dilation which is a transformation that makes an image proportionately smaller or larger by a scale factor. The scale factor is how much smaller or larger the shape will be, if the scale factor is between 0 and 1 then it will shrink, if it is greater than one then the image will stretch (be larger). In this case, the scale factor is 2, therefore the image will stretch. Since the center of dilation is the origin, to find the new coordinates simply multiply each x and y value by the scale factor. So A's original coordinates (-2,5) become (-4,10) and so forth. Therefore the equation for this dilation is (x, y) → (2x,2y).
Answer:
The system of equations has one solution. The two equations are intersecting lines.
Step-by-step explanation:
if you want to use the substitution method, you would have to plug in y for 12x+2 in the second equation.
2(12x+2)=x+4
next, you have to distribute
24x+4=x+4
subtract 24x from each side
4=-23x+4
subtract 4 from each side
0=23x
divide each side by 23
x=0
now, plug in 0 to one equation.
y=12(0)+2
y=2
the lines intersect at one point, (0,2)
Answer:
8
Step-by-step explanation:
1. 3b - 2 (1 - b) / a - 2
2. 3(2) - 2 (1 - 2) / 3 - 2
3. 6 - 2 (-1) / 1
4. 6 + 2 / 1
5. 8 / 1
6. 8
Answer:
1st Equation: -8x + y = 22
At (-2,6)
(-8*-2)+ 6 =16+6= 22: That is correct
2nd Equation: -8x - y =10
At (-2,6)
(-8*-2)-6= 16-6= 10: That is correct
Both are correct.
Hope it helps you.